Low-Frequency Electromechanical Oscillation Suppression of Hybrid Synchronous Sources Based on a Dual-Input Power System Stabilizer Strategy (International Conference on Energy, Intelligence Systems, and Cloud Computing (Ingenio 2026), 2026)
With the large-scale integration of renewable energy, hybrid power systems comprising virtual synchronous generators (VSGs) and synchronous generators (SGs) are increasingly susceptible to low-frequency electromechanical oscillations (LFEOs) caused by the dynamic interaction between virtual and physical inertia. This paper investigates the oscillatory characteristics and damping behavior of a VSG-SG hybrid synchronous-source system. A Phillips-Heffron small-signal model is developed to identify the dominant modes and reveal the virtual-physical power-angle coupling mechanism. A dual-input power system stabilizer (PSS2A) is then incorporated into the SG excitation system, and its LFEO suppression mechanism is analyzed using the damping-torque method. Eigenvalue analysis and time domain simulations under an applied disturbance show that PSS2A shifts the dominant oscillatory poles farther into the left half-plane, increases the damping ratio, and markedly reduces the power- and angle-oscillation amplitudes. The results demonstrate that PSS2A enhances the damping of SG-dominated modes while weakening the dynamic interaction between the SG rotor angle and the VSG virtual power angle. This study provides a theoretical basis for applying conventional dual-input stabilizers in VSG-SG hybrid power systems.
Keywords: VSG-SG hybrid synchronous-source system; Low frequency electromechanical oscillations; Power system stabilizer.